KOMPROMI HUKUM ISLAM DAN ADAT DALAM KEWARISAN PUSAKA TINGGI DI MINANGKABAU - Nuzul Iskandar (JISRAH: Jurnal Integrasi Ilmu Syariah, 2022)
This article is intended to explain the concept of pusaka tinggi in Minangkabau which is the result of a compromise between Islamic law and customary law. This study is a literature study on several manuscripts, consisting of al-Da’i al-Masmu’ fi Radd ala Man Yuritsu al-Ikhwah wa Awlad al-Ikhwah Ma’a Wujud al-Ushul wa al-Furu’, al-Manhaj al-Masyru’, and Jauhar al-Faridah fi al-Ajwabah al-Mufidah by Syekh Ahmad Khatib al-Minangkabawi; Sendi Aman Tiang Selamat and al-Fara’id by Syekh Abdul Karim Amrullah; and the writings of Mahjoeddin Datuk Soetan Maharadja which spread in several print media at that time. The results of the study show that the concept of pusaka tinggi in Minangkabau was born from a process of fierce debate, not only between religious leaders and traditional leaders, but also between fellow religious leaders, even between teachers and students. Initially, this debate was considered as an attempt to weaken the customary inheritance system applied by the Minangkabau people, but in reality it became a reinforcement of the existence of this inheritance. This debate actually provides additional legitimacy for the Minangkabau inheritance system, from previously only relying on customary legitimacy to having both customary and religious legitimacy, and then later being referred to as pusaka tinggi.